Battery negative electrode slurry and preparation method thereof, negative electrode plate, battery, assembly and equipment
By using additives incompatible with the solvent in the battery negative electrode slurry, a liquid bridge and a chain network is formed, which solves the cracking and curling problems of the battery negative electrode sheet during the preparation process, and achieves the improvement of high energy density and kinetic performance.
Patent Information
- Application Number
- CN202510495943.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2025-08-01
AI Technical Summary
The prior art is prone to cracking or crimping problems during the preparation of battery negative electrode sheets, and the existing improvement measures are limited in effect.
A battery negative electrode slurry containing negative electrode active material particles and additives incompatible with the solvent is used to generate a capillary suspension effect in the solvent through the additives, so that it is evenly dispersed and wetted with the negative electrode active material particles at the intersection of the two phases, forming a liquid bridge and a chain-like network to enhance the action force between the particles.
It effectively avoids problems such as cracking and curling of the electrode sheet. It is suitable for coating the negative electrode sheet of ultra-high surface density batteries, improving the energy density and dynamic performance of the battery.
Smart Images

Figure CN120413671A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and particularly to a battery negative electrode paste, a preparation method of a battery negative electrode paste, a battery negative electrode sheet, a battery, a battery assembly, and an electrical device. Background Art
[0002] In the process of preparing a battery negative electrode sheet, generally, a negative electrode paste can be thickly coated on the surface of a current collector to form a relatively thick electrode layer. However, due to factors such as the rheological properties of the paste, the coating process, and the drying conditions, the thickly coated paste usually easily causes the electrode sheet to crack or curl.
[0003] In the prior art, from the process level, by reducing the baking temperature, the air outlet rate, and the driving speed of the baking line, and slowly and repeatedly drying the electrode sheet multiple times, the cracking and curling of the electrode sheet can be reduced. However, this will reduce the production capacity of the production line, increase the difficulty of the coating and baking processes, and the improvement ability is limited. From the paste level, small molecule plasticizers, high boiling point organic solvents, polymers with high adhesion, and some organic solvents that can reduce the surface tension can be added, so as to avoid the cracking or curling of the electrode sheet to a certain extent by reducing the solvent evaporation rate, reducing the surface tension, and increasing the adhesion between the main materials. However, its improvement ability is also limited. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to provide a battery negative electrode paste and its preparation method, a battery negative electrode sheet, a battery, a battery assembly, and an electrical device, which can avoid the cracking or curling of the battery negative electrode sheet.
[0005] To solve the above problems, the present invention discloses a battery negative electrode paste, which includes a paste core component and a solvent, and the paste core component includes negative electrode active material particles and an additive;
[0006] Wherein, the additive is dispersed in the solvent and is incompatible with the solvent; the additive and the solvent jointly wet the negative electrode active material particles, so that the negative electrode active material particles are dispersed at the two-phase interface of the additive and the solvent.
[0007] Optionally, the ratio between the contact angle of the additive on the negative electrode active material particles and the contact angle of the solvent on the negative electrode active material particles is 1 / 4 - 1.
[0008] Optionally, the contact angle of the additive on the negative electrode active material particles is 30° - 75°.
[0009] Optionally, the additive includes polyethers and / or long-chain oligo-hydroxy alcohol compounds.
[0010] Optionally, the polyether compound includes at least one of polyether, polyoxyethylene, and polyether modifiers, and / or the long-chain oligo-hydroxy alcohol compound includes polymer oligoalcohol.
[0011] Optionally, the weight-average molecular weight of the additive is 200 - 4000.
[0012] Optionally, the mass percentage of the additive in the core components of the slurry is 0.05% - 0.5%.
[0013] Optionally, the mass ratio between the core components of the slurry and the solvent is 4:6 to 6:4.
[0014] Optionally, the negative electrode active material particles include one or a combination of natural graphite, artificial graphite, soft carbon, and hard carbon, wherein the artificial graphite includes at least one of petroleum coke graphite, needle coke graphite, coated graphite, and mesophase carbon microspheres.
[0015] Optionally, the core components of the slurry further include one or a combination of a dispersant, a conductive agent, and a binder.
[0016] An embodiment of the present invention further provides a method for preparing a battery negative electrode slurry as described in the embodiment of the present invention, and the method includes:
[0017] Mixing the negative electrode active material particles and the solvent to obtain a mixed material;
[0018] Adding an additive to the mixed material to obtain a battery negative electrode slurry.
[0019] An embodiment of the present invention further provides a method for preparing a battery negative electrode plate, and the method includes:
[0020] Coating a battery negative electrode slurry on a preset negative electrode current collector; wherein the battery negative electrode slurry is the battery negative electrode slurry described in the embodiment of the present invention, or the battery negative electrode slurry is a battery negative electrode slurry prepared by using the method for preparing a battery negative electrode slurry as described in the embodiment of the present invention;
[0021] Drying the negative electrode substrate coated with the battery negative electrode slurry to obtain a battery negative electrode plate.
[0022] An embodiment of the present invention further provides a battery, and the battery includes the battery negative electrode plate described in the embodiment of the present invention.
[0023] An embodiment of the present invention further provides a battery assembly, and the battery assembly includes the battery described in the embodiment of the present invention.
[0024] An embodiment of the present invention further provides an electrical device, and the electrical device includes the battery described in the embodiment of the present invention.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] Through the battery negative electrode paste provided by the embodiments of the present invention, the battery negative electrode paste includes a paste core component and a solvent, and the paste core component includes negative electrode active material particles and an additive; wherein, the additive is dispersed in the solvent and is incompatible with the solvent; the additive and the solvent jointly wet the negative electrode active material particles, so that the negative electrode active material particles are dispersed at the two-phase interface between the additive and the solvent. Thus, by mixing additives that are incompatible with the solvent, a capillary suspension effect is generated by the additives in the solvent, so that the additives are uniformly dispersed in the solvent. At the same time, by jointly wetting the negative electrode active material particles with the additive and the solvent, the negative electrode active material particles tend to be dispersed at the two-phase interface between the additive and the solvent. At the same time, the additive can fill the gaps between the negative electrode active material particles to form a liquid bridge. Through the action of the liquid bridge, the negative electrode active material particles can be connected to each other to form a chain-like network, so that the force between the negative electrode active material particles is further enhanced. Thereby reducing the sedimentation rate of the negative electrode active material particles in the paste, improving the uniformity and stability of the paste, and the strong force between the negative electrode active material particles can reduce the tendency of the battery negative electrode paste to spread and level outwards. Therefore, the electrode layer made of the battery negative electrode paste can be more uniform, avoiding problems such as cracking, curling, and warping of the electrode due to uneven surface density, and is suitable for coating of battery negative electrode sheets with ultra-high surface density. Moreover, the network structure retains a porous structure after the solvent evaporates, which can increase the porosity of the ultra-high surface density negative electrode sheet and is beneficial to the improvement of battery kinetics. Description of the Drawings
[0027] Figure 1 is a schematic diagram of the distribution of negative electrode active material particles in a battery negative electrode paste in the prior art;
[0028] Figure 2 is a schematic diagram of the distribution of negative electrode active material particles in a battery negative electrode paste in an embodiment of the present invention;
[0029] Figure 3 is a schematic diagram of the contact angle between an additive and graphite in an embodiment of the present invention;
[0030] Figure 4 is a schematic diagram of the cracking situation of the coating of a battery negative electrode paste in an embodiment of the present invention;
[0031] Figure 5 is an enlarged schematic diagram of the cracking situation of the coating of a battery negative electrode paste at 180°C in an embodiment of the present invention;
[0032] Figure 6 is a schematic diagram of the microscopic cracks of a battery negative electrode paste in an embodiment of the present invention. Detailed implementation mode
[0033] To make the above objects, features, and advantages of the present invention more obvious and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific implementation modes.
[0034] An embodiment of the present invention provides a battery negative electrode paste, which includes a paste core component and a solvent. The paste core component includes negative electrode active material particles and an additive;
[0035] Among them, the additive is dispersed in the solvent and is incompatible with the solvent; the additive and the solvent jointly wet the negative electrode active material particles, so that the negative electrode active material particles are dispersed at the two-phase interface of the additive and the solvent.
[0036] Specifically, the negative electrode active material particles can be materials used in the battery to store and release charge carriers at the negative electrode.
[0037] The negative electrode active material particles include one or a combination of natural graphite, artificial graphite, soft carbon, and hard carbon. The particle size D50 can be 5 μm to 20 μm.
[0038] Specifically, natural graphite can be a graphite material extracted from natural ore, which usually has a layered structure and has good cycle stability during charge and discharge.
[0039] Artificial graphite can be a graphite material prepared by high-temperature pyrolysis of organic compounds (such as petroleum coke, asphalt, etc.), and has good cycle stability during charge and discharge.
[0040] Among them, artificial graphite includes at least one of petroleum coke graphite, needle coke graphite, coated graphite, and mesophase carbon microspheres. Petroleum coke graphite can be artificial graphite prepared from conventional petroleum coke as raw material. Needle coke graphite can be artificial graphite prepared from needle-shaped petroleum coke as raw material. Mesophase carbon microspheres can be spherical carbon materials prepared by pyrolysis of organic compounds such as asphalt, which have a high specific capacity and good cycle stability, and the spherical structure is beneficial to the uniform coating and compaction of the electrode. Coated graphite can be artificial graphite obtained by forming one or more functional covering layers on the surface of graphite particles. The coating material can be a carbonaceous material (such as asphalt), a metal oxide (such as nickel oxide, copper oxide, iron oxide, etc.), a metal (such as nickel, zinc, silver, etc.), and the present invention does not limit this.
[0041] Soft carbon can be an amorphous carbon material with a low degree of graphitization. It can have a high specific capacity and good cycle stability.
[0042] Hard carbon can be an amorphous carbon material with a high degree of graphitization. It can also have a high specific capacity and good cycle stability.
[0043] In the embodiments of the present invention, in order to enable the negative electrode active material particles to be uniformly dispersed in the negative electrode slurry of the battery and avoid situations such as cracking and warping of the electrode due to uneven surface density. An additive can be added to the negative electrode slurry of the battery. The additive is immiscible with the solvent. In this case, after the additive is mixed into the solvent, a capillary suspension effect can be formed in the solvent, enabling the additive to be better dispersed in the solvent. At the same time, both the additive and the solvent can have wettability to the negative electrode active material particles, so that the additive in the solvent can jointly wet the negative electrode active material particles with the solvent. As a result, the negative electrode active material particles tend to be dispersed at the two-phase interface of the additive and the solvent. Thus, the negative electrode active material particles can be uniformly dispersed in the solvent together with the additive.
[0044] At the same time, the additive dispersed in the solvent can wet multiple adjacent particles simultaneously. Thus, the additive can act as if it fills the gaps between the negative electrode active material particles, forming a liquid bridge between the negative electrode active material particles. Through such a liquid bridge, the interaction force between the negative electrode active material particles can be increased, enabling the negative electrode active material particles to be connected to each other, and a chain-like network-like spanning network structure to be formed between the particles. Through the strong interaction force between the negative electrode active material particles, the tendency of the negative electrode slurry of the battery to spread and level outwards can be reduced, thereby reducing the sedimentation rate of the negative electrode active material particles in the slurry, improving the uniformity and stability of the slurry, avoiding problems such as cracking, curling, and warping of the electrode caused by uneven surface density, and being applicable to the coating of the negative electrode of the battery with an ultra-high surface density.
[0045] In addition, the chain-like network formed by the connection of the negative electrode active material particles to each other can play a supporting role during the drying process of the negative electrode of the battery in the subsequent process of manufacturing the negative electrode of the battery by the thick coating process, resisting the acting force generated by evaporation at the solid-liquid interface of the particles during evaporation, inhibiting the cracking of the electrode. At the same time, the network voids are left after the evaporation of the solvent, forming a multi-porous negative electrode of the battery. Thus, when the electrode layer coated on the negative electrode of the battery is relatively thick, while achieving a high energy density of the prepared battery, the battery kinetic performance can be improved. At the same time, due to the multi-porous structure of the negative electrode of the battery, the porosity of the negative electrode with an ultra-high surface density can be increased, which is also beneficial to the improvement of the battery kinetics.
[0046] As a specific example of the present invention, Figure 1It is a schematic diagram of the distribution of negative active material particles in the negative electrode slurry in the prior art. In the prior art, without adding additives, the negative active material particles can be dispersed in the solvent. During the process of preparing the negative electrode sheet of the battery, the negative electrode sheet of the battery can be subjected to evaporation drying treatment. During the evaporation drying process, as the solvent volatilizes, it may cause a local concentration difference in the negative electrode slurry of the battery, causing the negative active material particles to move unevenly in the negative electrode slurry of the battery as the solvent volatilizes, resulting in uneven surface coating density of the electrode layer on the negative electrode sheet of the battery. Different positions on the surface of the negative electrode sheet of the battery are subjected to different forces during the evaporation drying process, resulting in problems such as cracking, curling, and warping of the electrode sheet.
[0047] Figure 2 It is a schematic diagram of the distribution of negative active material particles in the negative electrode slurry in an embodiment of the present invention. In the embodiment of the present invention, the capillary suspension effect is generated by the additive in the solvent, so that the additive is uniformly dispersed in the solvent. At the same time, by jointly wetting the negative active material particles with the additive and the solvent, the negative active material particles can tend to be dispersed at the two-phase interface between the additive and the solvent, so that the particles can be uniformly dispersed in the negative electrode slurry of the battery. At the same time, the additive can fill the gaps between the negative active material particles to form a liquid bridge. Through the action of the liquid bridge, the negative active material particles can be connected to each other to form a chain-like network, further enhancing the force between the negative active material particles. The strong force between the negative active material particles can resist the force received during the evaporation drying process, and at the same time reduce the tendency of the negative electrode slurry of the battery to spread and level outwards. Therefore, the electrode layer made of the negative electrode slurry of the battery can be more uniform, and problems such as cracking, curling, and warping of the electrode sheet during the preparation of the ultra-thick negative electrode sheet of the battery can be avoided.
[0048] In an embodiment of the present invention, the ratio of the contact angle of the additive on the negative active material particles to the contact angle of the solvent on the negative active material particles is 1 / 4 - 1.
[0049] Specifically, in order to enable both the additive and the solvent to wet the negative electrode active material particles, and the negative electrode active material particles can be better dispersed at the two-phase interface of the solvent and the additive, the additive can be made to preferentially wet the negative electrode active material particles. Thus, the contact angle of the additive on the negative electrode active material particles can be no greater than the contact angle of the solvent on the negative electrode active material particles, so that the negative electrode active material particles tend to reduce the surface tension and are preferentially wetted by the additive. At the same time, the wettability of the additive and the solvent on the negative electrode active material particles should not differ too much, that is, the contact angle of the additive on the negative electrode active material particles and the contact angle of the solvent on the negative electrode active material particles should not differ too much. If the wettability of the additive and the solvent on the negative electrode active material particles differs too much, it may cause the negative electrode active material particles to be wetted only by the additive or only by the solvent, resulting in the agglomeration of the negative electrode active material particles around the solvent or the additive, which instead leads to a decline in the overall performance of the battery negative electrode paste.
[0050] Thus, the ratio between the contact angle of the additive on the negative electrode active material particles and the contact angle of the solvent on the negative electrode active material particles can be set to 1 / 4 - 1. Within this ratio range, the contact angle of the additive on the negative electrode active material particles and the contact angle of the solvent on the negative electrode active material particles do not differ too much, the negative electrode active material particles can be wetted by both the additive and the solvent, and the additive can preferentially wet the negative electrode active material particles, so that the negative electrode active material particles can be better dispersed in the battery negative electrode paste and form a chain-like network.
[0051] In a specific implementation, the additive and the solvent can be respectively dropped onto the surface of the negative electrode active material particles, and then the contact angle tester is used to respectively detect the contact angle of the additive on the negative electrode active material particles and the contact angle of the solvent on the negative electrode active material particles.
[0052] In an embodiment of the present invention, the contact angle of the additive on the negative electrode active material particles is 30° - 75°. For example, 30°, 35°, 40°, 45°, 50°, 55°, 60°, 65°, 70°, etc.
[0053] Specifically, when the contact angle of the additive on the negative electrode active material particles is relatively small, the additive can preferentially wet the negative electrode active material particles and can better form liquid bridges between the negative electrode active material particles. Through the liquid bridge effect, the negative electrode active material particles can be connected to each other to form a chain-like network, further improving the stability of the dispersion of the negative electrode active material particles in the battery negative electrode paste. Thus, an additive with a contact angle of 30° - 75° on the negative electrode active material particles under the condition of 25 ± 2°C can be selected.
[0054] As a specific example of the present invention, Figure 3It is a schematic diagram of the contact angle between the additive and graphite in the embodiments of the present invention. The contact angle of the additive on artificial graphite can be in a relatively small range of 30°-75°. The additive can have good wettability to artificial graphite, while the contact angle of a solvent such as water on artificial graphite is usually less than 80°. The wettability of both to artificial graphite is similar. When a small amount of the additive preferentially wets some areas of artificial graphite, the solvent can wet the remaining part of artificial graphite. Thus, the additive and the solvent can jointly wet the negative active material particles and disperse the negative active material particles at the two-phase junction of the additive and the solvent.
[0055] In one embodiment of the present invention, the additive includes polyether compounds and / or long-chain oligo-hydroxy alcohols.
[0056] Specifically, polyether compounds and / or long-chain oligo-hydroxy alcohols that are immiscible with water and have wettability to the negative active material particles can be selected as the additive. Thus, the additive and the solvent can jointly wet the negative active material particles and disperse the negative active material particles at the two-phase junction of the additive and the solvent.
[0057] Specifically, the polyether compounds can include polyethers, polyethylene oxides, polyether modifiers, etc. The long-chain oligo-hydroxy alcohols can include polymer oligo-alcohols. Among them, the polyether modifiers can include at least one of polyether-modified silicone oil, polyether-modified fluorosilicone oil, and fluorine-modified polyether.
[0058] Generally speaking, when the molar number of ethylene oxide addition (EO number) of polyether compounds is low, and the molecular weight is high or the carbon chain is long, it is difficult for them to be miscible with the solvent. By modifying the polyether to graft materials that are difficult to be miscible with the solvent, such as silicone oil, fluorosilicone oil, fluorine, etc., polyether modifiers can be obtained, and polyether compounds that are also difficult to be miscible with the solvent can be obtained.
[0059] Long-chain oligo-hydroxy alcohols such as polymer oligo-alcohols usually have long carbon chains, making them also difficult to be miscible with the solvent.
[0060] At the same time, polyether compounds and long-chain oligo-hydroxy alcohols usually have a small contact angle on the graphite surface, enabling them to have good wetting performance for the negative active material particles. Thus, they can be dispersed in the solvent as additives to form a liquid bridge between the negative active material particles. Through such a liquid bridge, the interaction force between the negative active material particles can be increased, causing the negative active material particles to be connected to each other to form a chain-like network.
[0061] In one embodiment of the present invention, the solvent includes water. The contact angle of water on the surface of the negative electrode active material particles can generally be less than 80°, and it can be relatively similar to the contact angle of the additive on the surface of the negative electrode active material particles, so that the additive and water can jointly wet the negative electrode active material particles.
[0062] In one embodiment of the present invention, the weight average molecular weight of the additive is 200 - 4000.
[0063] The weight average molecular weight can be used to describe the molecular weight distribution in a polymer sample. When the weight average molecular weight of the additive is 200 - 4000, due to the relatively large molecular weight, the additive can be more inclined to be immiscible with the solvent, and the weight average molecular weight does not exceed 4000, avoiding the situation where the additive cannot be well dispersed in the solvent due to too large a molecular weight.
[0064] In one embodiment of the present invention, the mass percentage of the additive in the core components of the slurry is 0.05% - 0.5%.
[0065] Specifically, with the change of the addition amount, the state of the additive in the solvent can be different. When the content of the additive is relatively low, the additive can present a pendulum state in the solvent. When the content of the additive is relatively high, the additive can present a Pickering emulsion state in the solvent. If the content of the additive further increases, inversion may occur. Therefore, in order to enable the additive to preferably form a capillary suspension state and be uniformly dispersed in the solvent, the mass percentage of the additive in the core components of the slurry can be set to 0.05% - 0.5%. Among them, the mass percentage can be 0.05%, 0.07%, 0.8%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, etc., and the present invention does not limit this.
[0066] At the same time, when the mass percentage of the additive in the core components of the slurry is 0.05% - 0.5%, the additive will not have adverse effects such as changing the viscosity of the battery negative electrode slurry and causing processing difficulties, or leaving too much non-battery active material and deteriorating the battery kinetic performance. Instead, the additive can prevent the cracking of the battery negative electrode material and enable the coating of an ultra-thick electrode layer.
[0067] In one embodiment of the present invention, preferably, the mass percentage of the additive in the core components of the slurry is 0.08% - 0.2%.
[0068] In a specific implementation, the mass percentage of the additive in the core components of the slurry is 0.08% - 0.2%. At this ratio, the addition amount of the additive is relatively small, which can better reduce the residue in the battery negative electrode sheet. At the same time, the additive can still preferably connect the negative electrode active material particles to form a chain-like network.
[0069] In one embodiment of the present invention, the mass ratio between the core components of the slurry and the solvent is 4:6 to 6:4. Among them, the mass ratio can be 4:6, 5:5, 5.5:4.5, 6:4, etc., and the present invention does not limit this.
[0070] In a specific implementation, the mass ratio between the core components of the slurry and the solvent can be 4:6 to 6:4. At this time, the proportions of the negative electrode active material particles, the additive, and the solvent are appropriate, and the additive and the solvent can preferably jointly wet the negative electrode active material particles. The negative electrode active material particles tend to be dispersed at the two-phase interface between the additive and the solvent, so that the particles can be in a state of being uniformly dispersed in the battery negative electrode slurry.
[0071] In one embodiment of the present invention, the core components of the slurry further include one or a combination of a dispersant, a conductive agent, and a binder.
[0072] Specifically, one or a combination of a dispersant, a conductive agent, and a binder can be further added to the core components of the slurry to optimize the performance of the battery negative electrode slurry.
[0073] Specifically, the dispersant can assist the negative electrode active material particles to be uniformly dispersed in the solvent, prevent the particles from agglomerating, and thus improve the uniformity and stability of the slurry. The dispersant can be sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), polyvinylpyrrolidone (PVP), etc.
[0074] The conductive agent can improve the conductivity of the negative electrode material, ensure that electrons can be quickly transmitted, and thus improve the charge-discharge efficiency and cycle life of the battery. Generally speaking, the conductive agent can include one or a combination of carbon black, carbon nanotubes, and graphene.
[0075] The binder can bond solid materials such as the negative electrode active material and the conductive agent together to form a stable electrode structure and prevent the materials from falling off and pulverizing during the charge-discharge process. The binder can be one or a combination of acrylic acid (PAA), acrylonitrile (PAN), styrene-butadiene rubber (SBR), and polyacrylate.
[0076] The embodiment of the present invention also provides a preparation method of the battery negative electrode slurry as in the embodiment of the present invention. The method includes:
[0077] Step 101: Mix the negative electrode active material particles and the solvent to obtain a mixture;
[0078] Step 102: Add an additive to the mixture to obtain the battery negative electrode slurry.
[0079] In a specific implementation, a part of the solvent can be first taken and mixed with the negative electrode active material particles, so that the negative electrode active material particles can be uniformly dispersed in the solvent. And because not all of the solvent is added, the solid content in the mixture is relatively high. At this time, the negative electrode active material particles can have good contact with each other and there can be a certain force between them, which is beneficial to the uniform dispersion of the negative electrode active material particles in the solvent and can reduce the dispersion time of the slurry. Subsequently, the remaining solvent is continuously added until the battery negative electrode slurry reaches the predetermined solid content, and the negative electrode active material particles can still maintain good dispersibility with each other.
[0080] Subsequently, an additive can be added to the mixture. The negative electrode active material particles are simultaneously wetted by the additive and the solvent, so that the negative electrode active material particles are dispersed at the two-phase interface between the additive and the solvent. Thus, by mixing additives that are immiscible with the solvent, a capillary suspension effect is generated by the additives in the solvent, making the additives uniformly dispersed in the solvent. At the same time, by jointly wetting the negative electrode active material particles with the additive and the solvent, the negative electrode active material particles tend to be dispersed at the two-phase interface between the additive and the solvent. Meanwhile, the additive can fill the gaps between the negative electrode active material particles to form a liquid bridge. Through the action of the liquid bridge, the negative electrode active material particles can be connected to each other to form a chain-like network, further enhancing the force between the negative electrode active material particles. As a result, the negative electrode active material particles can be uniformly dispersed in the solvent, and the strong force between the negative electrode active material particles can resist the force during the evaporation drying process and reduce the tendency of the battery negative electrode slurry to spread and level outwards. Therefore, the electrode layer made of the battery negative electrode slurry can be more uniform, avoiding problems such as cracking, curling, and warping of the electrode sheet caused by uneven surface density, and is suitable for coating high-surface-density battery negative electrode sheets.
[0081] Optionally, when a dispersant, a conductive agent, or a combination thereof is needed, the dispersant and the conductive agent can be mixed with the negative electrode active material particles and then dispersed together in the solvent to ensure that the dispersant, the conductive agent, and the negative electrode active material particles can all be uniformly dispersed.
[0082] For the binder, after mixing the negative electrode active material particles and the solvent to obtain a mixture, the binder is added. At this time, the battery negative electrode slurry reaches the predetermined solid content, and the negative electrode active material particles are well dispersed. At this time, the binder is added under the condition of high-power mechanical stirring to avoid excessive local viscosity of the slurry and ensure uniform viscosity in the slurry. After the addition of the binder is completed, an additive is added to make the additive and the solvent wet the negative electrode active material particles simultaneously.
[0083] In a specific implementation, to facilitate the subsequent coating of the battery negative electrode slurry, the viscosity of the battery negative electrode slurry at 50 / s can be adjusted to 1000 - 4000 mPa·s.
[0084] An embodiment of the present invention also provides a method for preparing a negative electrode sheet of a battery, the method comprising:
[0085] Step 201, coating a negative electrode slurry of the battery on a preset negative electrode current collector; wherein, the negative electrode slurry of the battery is the negative electrode slurry of the embodiment of the present invention, or the negative electrode slurry of the battery is prepared by using the preparation method of the negative electrode slurry of the embodiment of the present invention;
[0086] Step 202, drying the negative electrode substrate coated with the negative electrode slurry to obtain a negative electrode sheet of the battery.
[0087] In a specific implementation, after the preparation of the negative electrode slurry of the battery is completed, the negative electrode slurry of the battery can be used to prepare a negative electrode sheet of the battery, and the negative electrode slurry of the battery can be coated on the negative electrode current collector.
[0088] Since the negative electrode active material particles in the negative electrode slurry prepared in the embodiment of the present invention can be well dispersed in the solvent and will not cause problems such as cracking of the electrode sheet due to uneven stress during the drying process, therefore, the coating thickness of the negative electrode slurry in the embodiment of the present invention can be relatively large, and the areal density can be between 280 g / m 2 ~400 g / m 2 If the thickness of the negative electrode current collector is 6 μm - 120 μm, the thickness of the prepared negative electrode sheet of the battery can be 80 - 400 μm.
[0089] In a specific implementation, the coating method of the negative electrode slurry can include methods such as a doctor blade method, a roll coating transfer method, a slot extrusion method, etc., and the present invention does not limit this.
[0090] In the embodiment of the present invention, under the capillary suspension action of the additive, during the leveling process of the negative electrode slurry, the negative electrode active material particles at the edge can be affected by the force from other negative electrode active material particles in the negative electrode slurry through the chain-like network, so that the negative electrode active material particles at the edge can be affected by an inward force, introducing the tendency of the slurry to diffuse and level outward, thereby reducing the thinning area of the negative electrode sheet and forming a more uniform coating.
[0091] Thereafter, the negative electrode substrate coated with the negative electrode slurry can be dried to obtain a negative electrode sheet of the battery. During the drying process, the chain-like network can play a supporting role in the negative electrode sheet of the battery, resisting the force generated by the evaporation at the solid-liquid interface of the particles during the evaporation process, inhibiting the cracking of the electrode sheet, and at the same time, the network voids are left after the solvent evaporates, forming a porous negative electrode sheet of the battery. Thus, when the electrode layer coated on the negative electrode sheet of the battery is relatively thick, while maintaining the high energy density of the battery, the battery kinetic performance is improved.
[0092] An embodiment of the present invention further provides a battery, which includes the battery negative electrode plate of the embodiment of the present invention.
[0093] In a specific implementation, when the battery includes the battery negative electrode plate of an embodiment of the present invention, the inter-particle force is stronger during the drying process of the electrode made of the battery negative electrode slurry, and the electrode layer can be more uniform, avoiding problems such as cracking, curling, and warping of the electrode plate caused by uneven surface density. Even when the electrode layer coated on the battery negative electrode plate is thicker, good battery dynamic performance can also be maintained.
[0094] Among them, the active material in the positive electrode plate of the battery can be lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, ternary positive electrode, nickel-rich oxide, etc., and the present invention does not impose any restrictions on this.
[0095] An embodiment of the present invention further provides a battery assembly, which includes the battery described in the embodiment of the present invention.
[0096] The battery assembly may be a battery module, a battery system, a battery stack, a battery array, etc., and the present invention does not impose any restrictions on this.
[0097] An embodiment of the present invention further provides an electric device, which includes the battery according to the embodiment of the present invention.
[0098] Among them, the electrical equipment can be 3C electronic equipment, new energy vehicles, electric bicycles, etc., and the present invention does not limit this.
[0099] In order to enable those skilled in the art to better understand the present invention, the battery negative electrode slurry according to the embodiments of the present invention is described below through multiple specific examples.
[0100] Example 1
[0101] The battery negative electrode slurry contains: 96.0% petroleum coke graphite (particle size D50 is 10μm), 1% dispersant sodium carboxymethyl cellulose, 1% binder styrene-butadiene rubber (SBR), 1.9% conductive agent carbon black, 0.1% additive polyether with a weight-average molecular weight (Mn) of 1000, whose contact angle with graphite is 60°-65°, and the solvent is deionized water.
[0102] (1) Dry mixing: mixing the negative electrode active material particles, dispersant, and conductive agent to obtain a dry mixed material A;
[0103] (2) Kneading: Add deionized water to the dry mixed material A until the solid content reaches 70%, and stir and knead for 40-120 min to obtain kneaded material B;
[0104] (3) Dispersion: Add deionized water to the kneaded material B until the solid content reaches 50%, and disperse for 60-120 minutes to obtain the mixed material C;
[0105] (4) Viscosity adjustment: Add a binder to the mixture C, and add deionized water to adjust the viscosity of the slurry so that the viscosity at 1 / s is 10,000 - 20,000 mPa·s and the viscosity at 50 / s is 3,000 - 4,000 mPa·s (measured by a rheometer) to obtain slurry D;
[0106] (5) Additive addition: Add an additive to slurry D and disperse for 10 - 40 min to obtain the battery negative electrode slurry.
[0107] (6) Preparation of negative electrode sheet: On the negative electrode current collector copper foil, coat the battery negative electrode slurry prepared in Example 1 in sequence according to the double-sided coating density of 260 g / m 2 、280 g / m 2 、300 g / m 2 、400 g / m 2 After drying at 180°C and rolling, obtain the battery negative electrode sheet.
[0108] Example 2
[0109] The battery negative electrode slurry contains: petroleum coke graphite (particle size D50 is 10 μm) 96.0%, dispersant sodium carboxymethyl cellulose 1%, binder styrene-butadiene rubber (SBR) 1%, conductive agent carbon black 1.9%, additive is 0.1% polyoxyethylene with a weight average molecular weight (Mn) of 2,000, the contact angle with graphite is 68° - 75°, and the solvent is deionized water.
[0110] (1) Dry mixing: Mix the negative electrode active material particles, dispersant, and conductive agent to obtain dry-mixed mixture A;
[0111] (2) Kneading: Add deionized water to the dry-mixed mixture A until the solid content is 70%, and perform stirring and kneading for 40 - 120 min to obtain kneaded mixture B;
[0112] (3) Dispersion: Add deionized water to the kneaded mixture B until the solid content is 50%, and disperse for 60 - 120 min to obtain mixture C;
[0113] (4) Viscosity adjustment: Add a binder to the mixture C, and add deionized water to adjust the viscosity of the slurry so that the viscosity at 1 / s is 10,000 - 20,000 mPa·s and the viscosity at 50 / s is 3,000 - 4,000 mPa·s (measured by a rheometer) to obtain slurry D;
[0114] (5) Additive addition: Add an additive to slurry D and disperse for 10 - 40 min to obtain the battery negative electrode slurry.
[0115] (6) Preparation of negative electrode sheet: On the negative electrode current collector copper foil, coat in sequence according to the double-sided coating density of 260 g / m 2 、280 g / m 2, 300 g / m 2 , 400 g / m 2 Coat the negative electrode paste of Example 1 in sequence. After drying at 180 °C and rolling, a negative electrode sheet of the battery is obtained.
[0116] Example 3
[0117] The negative electrode paste of the battery contains: 96.0% of petroleum coke graphite (particle size D50 is 10 μm), 1% of dispersant sodium carboxymethyl cellulose, 1% of binder styrene-butadiene rubber (SBR), 1.9% of conductive agent carbon black, 0.1% of additive polymer oligol with a weight average molecular weight (Mn) of 300, the contact angle with graphite is 46° - 52°, and the solvent is deionized water.
[0118] (1) Dry mixing: Mix the negative electrode active material particles, dispersant, and conductive agent, and dry mix to obtain mixture A;
[0119] (2) Kneading: Add deionized water to dry mixture A to a solid content of 70%, stir and knead for 40 - 120 min to obtain kneaded material B;
[0120] (3) Dispersion: Add deionized water to kneaded material B to a solid content of 50%, disperse for 60 - 120 min to obtain mixture C;
[0121] (4) Viscosity adjustment: Add a binder to mixture C, and add deionized water to adjust the viscosity of the paste so that the viscosity at 1 / s is 10000 - 20000 mPa·s and the viscosity at 50 / s is 3000 - 4000 mPa·s (measured by a rheometer) to obtain paste D;
[0122] (5) Additive addition: Add an additive to paste D, disperse for 10 - 40 min to obtain the negative electrode paste of the battery.
[0123] (6) Preparation of negative electrode sheet: On the negative electrode current collector copper foil, coat the negative electrode paste of Example 1 in sequence at a double-sided coating density of 260 g / m 2 , 280 g / m 2 , 300 g / m 2 , 400 g / m 2 Coat the negative electrode paste of Example 1 in sequence. After drying at 180 °C and rolling, a negative electrode sheet of the battery is obtained.
[0124] Example 4
[0125] The battery anode paste contains: 96.0% of petroleum coke graphite (particle size D50 is 10 μm), 1% of dispersant sodium carboxymethyl cellulose, 1% of binder styrene-butadiene rubber (SBR), 1.9% of conductive agent carbon black, 0.1% of additive polyether-modified silicone oil with a weight average molecular weight (Mn) of 1000, the contact angle with graphite is 46°-52°, and the solvent is deionized water.
[0126] (1) Dry mixing: Mix the anode active material particles, dispersant, and conductive agent, and dry mix to obtain mixture A;
[0127] (2) Kneading: Add deionized water to dry mixture A until the solid content is 70%, stir and knead for 40 - 120 min to obtain kneaded material B;
[0128] (3) Dispersion: Add deionized water to kneaded material B until the solid content is 50%, disperse for 60 - 120 min to obtain mixture C;
[0129] (4) Viscosity adjustment: Add binder to mixture C, add deionized water to adjust the paste viscosity so that the viscosity at 1 / s is 10000 - 20000 mPa·s and the viscosity at 50 / s is 3000 - 4000 mPa·s (measured by a rheometer) to obtain paste D;
[0130] (5) Additive addition: Add the additive to paste D, disperse for 10 - 40 min to obtain the battery anode paste.
[0131] (6) Anode sheet preparation: On the anode current collector copper foil, coat the battery anode paste prepared in Example 1 successively at coating densities of 260 g / m 2 、280 g / m 2 、300 g / m 2 、400 g / m 2 After drying at 180°C and rolling, obtain the battery anode sheet.
[0132] Example 5
[0133] The battery anode paste contains: 96.0% of pitch-coated graphite, 1% of dispersant sodium carboxymethyl cellulose, 1% of binder styrene-butadiene rubber (SBR), 1.9% of conductive agent carbon black, 0.1% of additive polyoxyethylene with a weight average molecular weight (Mn) of 2000, the contact angle with graphite is 68°-75°, and the solvent is deionized water.
[0134] (1) Dry mixing: Mix the anode active material particles, dispersant, and conductive agent, and dry mix to obtain mixture A;
[0135] (2) Kneading: Add deionized water to dry mixture A until the solid content is 70%, stir and knead for 40 - 120 min to obtain kneaded material B;
[0136] (3) Dispersion: Deionized water was added to kneaded material B until the solid content reached 50%, and after dispersion for 60 - 120 min, mixture C was obtained.
[0137] (4) Viscosity adjustment: A binder was added to mixture C, and deionized water was added to adjust the viscosity of the slurry so that the viscosity at 1 / s was in the range of 10000 - 20000 mPa·s and the viscosity at 50 / s was 3000 - 4000 mPa·s (measured by a rheometer), obtaining slurry D.
[0138] (5) Additive addition: An additive was added to slurry D and dispersed for 10 - 40 min to obtain the battery anode slurry.
[0139] (6) Preparation of anode sheet: On the anode current collector copper foil, the battery anode slurry prepared in Example 1 was coated successively at double-sided coating densities of 260 g / m 2 , 280 g / m 2 , 300 g / m 2 , 400 g / m 2 After drying at 180°C and rolling, the battery anode sheet was obtained.
[0140] Example 6
[0141] The battery anode slurry contains: needle coke graphite 96.0%, dispersant sodium carboxymethyl cellulose 1%, binder styrene-butadiene rubber (SBR) 1%, conductive agent carbon black 1.9%, additive 0.1% polyoxyethylene with a weight average molecular weight (Mn) of 2000, the contact angle with graphite is 68° - 75°, and the solvent is deionized water.
[0142] (1) Dry mixing: The anode active material particles, dispersant, and conductive agent were mixed to obtain dry-mixed mixture A.
[0143] (2) Kneading: Deionized water was added to dry-mixed mixture A until the solid content reached 70%, and stirring and kneading were carried out for 40 - 120 min to obtain kneaded material B.
[0144] (3) Dispersion: Deionized water was added to kneaded material B until the solid content reached 50%, and after dispersion for 60 - 120 min, mixture C was obtained.
[0145] (4) Viscosity adjustment: A binder was added to mixture C, and deionized water was added to adjust the viscosity of the slurry so that the viscosity at 1 / s was in the range of 10000 - 20000 mPa·s and the viscosity at 50 / s was 3000 - 4000 mPa·s (measured by a rheometer), obtaining slurry D.
[0146] (5) Additive addition: An additive was added to slurry D and dispersed for 10 - 40 min to obtain the battery anode slurry.
[0147] (6) Preparation of negative electrode sheet: On the negative electrode current collector copper foil, the negative electrode slurry prepared in Example 1 was coated successively at double-sided coating densities of 260 g / m 2 , 280 g / m 2 , 300 g / m 2 , 400 g / m 2 After drying at 180°C and rolling, the negative electrode sheet of the battery was obtained.
[0148] Example 7
[0149] The negative electrode slurry of the battery comprises: 96.0% of petroleum coke graphite (particle size D50 is 15 μm), 1% of dispersant sodium carboxymethyl cellulose, 1% of binder styrene-butadiene rubber (SBR), 1.9% of conductive agent carbon black, 0.1% of additive polyoxyethylene with a weight average molecular weight (Mn) of 2000, the contact angle with graphite is 68° - 75°, and the solvent is deionized water.
[0150] (1) Dry mixing: Mix the negative electrode active material particles, dispersant, and conductive agent to obtain dry mixed mixture A;
[0151] (2) Kneading: Add deionized water to dry mixed mixture A until the solid content is 70%, stir and knead for 40 - 120 min to obtain kneaded mixture B;
[0152] (3) Dispersion: Add deionized water to kneaded mixture B until the solid content is 50%, disperse for 60 - 120 min to obtain mixture C;
[0153] (4) Viscosity adjustment: Add binder to mixture C, add deionized water to adjust the slurry viscosity so that the viscosity at 1 / s is 10000 - 20000 mPa·s and the viscosity at 50 / s is 3000 - 4000 mPa·s (tested by a rheometer) to obtain slurry D;
[0154] (5) Addition of additive: Add additive to slurry D, disperse for 10 - 40 min to obtain the negative electrode slurry of the battery.
[0155] (6) Preparation of negative electrode sheet: On the negative electrode current collector copper foil, the negative electrode slurry prepared in Example 1 was coated successively at double-sided coating densities of 260 g / m 2 , 280 g / m 2 , 300 g / m 2 , 400 g / m 2 After drying at 180°C and rolling, the negative electrode sheet of the battery was obtained.
[0156] Comparative Example 1
[0157] The battery negative electrode slurry contains: 96.0% of petroleum coke graphite (particle size D50 is 10 μm), 1% of dispersant sodium carboxymethyl cellulose, 1% of binder styrene-butadiene rubber (SBR), 1.9% of conductive agent carbon black, and the solvent is deionized water.
[0158] (1) Dry mixing: Mix the negative electrode active material particles, dispersant, and conductive agent, and dry mix to obtain mixture A;
[0159] (2) Kneading: Add deionized water to dry mix mixture A until the solid content is 70%, and stir and knead for 40 - 120 min to obtain kneaded mixture B;
[0160] (3) Dispersion: Add deionized water to kneaded mixture B until the solid content is 50%, and disperse for 60 - 120 min to obtain mixture C;
[0161] (4) Viscosity adjustment: Add the binder to mixture C, and add deionized water to adjust the slurry viscosity so that the viscosity at 1 / s is 10000 - 20000 mPa·s and the viscosity at 50 / s is 3000 - 4000 mPa·s (measured by a rheometer) to obtain slurry D;
[0162] (5) Preparation of negative electrode sheet: On the negative electrode current collector copper foil, coat the battery negative electrode slurry prepared in Example 1 in sequence at double-sided coating densities of 260 g / m 2 、280 g / m 2 、300 g / m 2 、400 g / m 2 After drying at 180°C and rolling, obtain the battery negative electrode sheet.
[0163] Comparative Example 2
[0164] The battery negative electrode slurry contains: 96.0% of petroleum coke graphite (particle size D50 is 10 μm), 1% of dispersant sodium carboxymethyl cellulose, 1% of binder styrene-butadiene rubber (SBR), 1.9% of conductive agent carbon black, 0.1% of additive N-methylpyrrolidone (NMP), and the solvent is deionized water.
[0165] (1) Dry mixing: Mix the negative electrode active material particles, dispersant, and conductive agent, and dry mix to obtain mixture A;
[0166] (2) Kneading: Add deionized water to dry mix mixture A until the solid content is 70%, and stir and knead for 40 - 120 min to obtain kneaded mixture B;
[0167] (3) Dispersion: Add deionized water to kneaded mixture B until the solid content is 50%, and disperse for 60 - 120 min to obtain mixture C;
[0168] (4) Viscosity adjustment: Add a binder to the mixture C, and add deionized water to adjust the viscosity of the slurry so that the viscosity at 1 / s is 10,000 - 20,000 mPa·s and the viscosity at 50 / s is 3,000 - 4,000 mPa·s (measured by a rheometer) to obtain slurry D;
[0169] (5) Additive addition: Add an additive to the slurry D and disperse for 10 - 40 min to obtain the battery negative electrode slurry.
[0170] (6) Preparation of negative electrode sheet: On the negative electrode current collector copper foil, coat the battery negative electrode slurry prepared in Example 1 in sequence according to the double-sided coating density of 260 g / m 2 、280 g / m 2 、300 g / m 2 、400 g / m 2 After drying at 180°C and rolling, obtain the battery negative electrode sheet.
[0171] Comparative Example 3
[0172] The battery negative electrode slurry contains: 96.0% petroleum coke graphite (particle size D50 is 10 μm), 1% dispersant sodium carboxymethyl cellulose, 1% binder styrene-butadiene rubber (SBR), 1.9% conductive agent carbon black, 0.1% additive 1,3-butanediol, and the solvent is deionized water.
[0173] (1) Dry mixing: Mix the negative electrode active material particles, dispersant, and conductive agent to obtain dry-mixed mixture A;
[0174] (2) Kneading: Add deionized water to the dry-mixed mixture A to a solid content of 70%, stir and knead for 40 - 120 min to obtain kneaded material B;
[0175] (3) Dispersion: Add deionized water to the kneaded material B to a solid content of 50%, disperse for 60 - 120 min to obtain mixture C;
[0176] (4) Viscosity adjustment: Add a binder to the mixture C, and add deionized water to adjust the viscosity of the slurry so that the viscosity at 1 / s is 10,000 - 20,000 mPa·s and the viscosity at 50 / s is 3,000 - 4,000 mPa·s (measured by a rheometer) to obtain slurry D;
[0177] (5) Additive addition: Add an additive to the slurry D and disperse for 10 - 40 min to obtain the battery negative electrode slurry.
[0178] (6) Preparation of negative electrode sheet: On the negative electrode current collector copper foil, coat in sequence according to the double-sided coating density of 260 g / m 2 、280 g / m 2 、300 g / m 2 、400 g / m2 The battery negative electrode slurry prepared in Example 1 was coated successively. After drying at 180 °C and rolling, the battery negative electrode sheet was obtained.
[0179] Through the battery negative electrode slurry provided by the embodiments of the present invention, the battery negative electrode slurry includes a slurry core component and a solvent. The slurry core component includes negative electrode active material particles and an additive. Among them, the additive is dispersed in the solvent and is incompatible with the solvent. The additive and the solvent jointly wet the negative electrode active material particles, so that the negative electrode active material particles are dispersed at the two-phase junction of the additive and the solvent. Thus, by mixing additives that are incompatible with the solvent, a capillary suspension effect is generated by the additive in the solvent, so that the additive is uniformly dispersed in the solvent. At the same time, by jointly wetting the negative electrode active material particles with the additive and the solvent, the negative electrode active material particles tend to be dispersed at the two-phase junction between the additive and the solvent. At the same time, the additive can fill the gaps between the negative electrode active material particles to form a liquid bridge. Through the action of the liquid bridge, the negative electrode active material particles can be connected to each other to form a chain-like network, so that the force between the negative electrode active material particles is further enhanced, resisting the force received during the evaporation drying process. And the negative electrode active material particles can be uniformly dispersed in the solvent, and the strong force between the negative electrode active material particles can reduce the tendency of the battery negative electrode slurry to spread and level outwards. Therefore, the electrode layer made of the battery negative electrode slurry can be more uniform, avoiding problems such as cracking, curling, and warping of the electrode sheet caused by uneven stress on the electrode sheet, and is suitable for coating of battery negative electrode sheets with ultra-high areal density. The cross-linked network structure retains a porous structure after solvent evaporation, which can increase the porosity of the electrode sheet and improve the problem of long ion transport paths in thick electrodes, realizing the improvement of the energy density of the battery and the improvement of kinetic performance.
[0180] The following specific experimental data are used to illustrate some advantages of the embodiments of the present invention compared with the prior art.
[0181] Coating cracking test
[0182] Figure 4 is a schematic diagram of the coating cracking situation of the battery negative electrode slurry in the embodiments of the present invention. The battery negative electrode sheets with a double-sided coating areal density of 300 g / m 2 in Comparative Example 1 and Example 1 were compared. They were respectively placed in an oven at 120 °C, 150 °C, and 180 °C, and the coating cracking situations were compared. The results are as Figure 4 shown.
[0183] It can be seen that in the case of no additive added in Comparative Example 1, a certain degree of cracking occurred in the areas indicated by the white circles on the battery negative electrode sheets of Comparative Example 1, while no cracking occurred in the examples with the additive added.
[0184] Specifically, Figure 5 is an enlarged schematic diagram of the cracking situation of the battery negative electrode paste coating in the embodiment of the present invention. It can be seen that in Comparative Example 1, cracking occurred in the area indicated by the white circle during baking at 180°C, while in Example 1, no cracking occurred during baking at 180°C. It can be seen that the addition of the additive effectively avoids problems such as cracking, curling, and warping of the electrode caused by uneven surface density.
[0185] Figure 6 is a schematic diagram of the microcracks of the battery negative electrode paste in the embodiment of the present invention. The negative electrode sheets of the battery with a double-sided coating surface density of 300 g / m 2 in Comparative Example 1 and Example 1 were compared. It can be seen that there were cracking situations in the negative electrode sheets of the battery in Comparative Example 1 under microscopic observation, while there were no cracking situations in the negative electrode sheets of the battery in Example 1. The addition of the additive effectively avoids problems such as cracking, curling, and warping of the electrode caused by uneven surface density.
[0186] The negative electrode sheets of the battery prepared in Examples 1-7 and Comparative Examples 1-3 were baked at 180°C, and the cracking situation was observed. Specifically, for the negative electrode sheets of the battery prepared in any of the examples, taking two negative electrode sheets of the battery as a group, three groups with different double-sided coating surface densities were taken for testing, and the cracking situation during baking was observed. If there was no cracking situation, it was represented as "√", and if at least one negative electrode sheet of the battery showed cracking, it was represented as "×". The results are shown in Table 1.
[0187] Double-sided coating density <![CDATA[260g / m 2 > <![CDATA[280g / m 2 > <![CDATA[300g / m 2 > <![CDATA[400g / m 2 > Example 1 √√√ √√√ √√√ √×× Example 2 √√√ √√√ √√√ √√√ Example 3 √√√ √√√ √√√ √√× Example 4 √√√ √√√ √√√ ××× Example 5 √√√ √√√ √√√ ××× Example 6 √√√ √√√ √√× ××× Example 7 √√√ √√√ √√√ √√√ Comparative Example 1 √√× √×× ××× ××× Comparative Example 2 √√√ √√× ××× ××× Comparative Example 3 √√√ √√√ ××× ×××
[0188] It can be seen that for the negative electrode sheets of the battery prepared in Examples 1-7 of the present invention, when the double-sided coating density was 260 g / m 2 and 280 g / m 2 , no cracking occurred. When the double-sided coating density was 300 g / m 2 , only one group of negative electrode sheets of the battery in Example 6 using needle coke graphite showed cracking. When the double-sided coating density was 400 g / m 2 , there were still no cracks in Examples 2 and 7 using polyoxyethylene as the additive.
[0189] For Comparative Example 1 without adding an additive, one group of cracks had already occurred when the double-sided coating density was 260 g / m 2 . For Comparative Example 2 using N-methylpyrrolidone (NMP) as an additive, one group of cracks occurred when the double-sided coating density was 280 g / m 2 . Comparative Examples 1, 2, and Comparative Example 3 using 1,3-butanediol as an additive could not achieve non-cracking at double-sided coating densities of 300 g / m 2 and 400 g / m2 remain uncracked under the following circumstances.
[0190] Specifically, although N-methylpyrrolidone added in Comparative Example 2 and 1,3-butanediol added in Comparative Example 3 also act on the negative electrode slurry of the battery and to a certain extent inhibit the cracking of the electrode sheet. However, the mechanism of inhibiting the cracking of the battery electrode sheet in Comparative Example 2 and Comparative Example 3 is different from that of the embodiments of the present invention.
[0191] For N-methylpyrrolidone, it mainly dissolves in the solvent by itself, and reduces the overall surface tension of the solvent through its own low surface tension, thereby inhibiting the capillary pressure generated due to solvent evaporation during the drying process of the electrode sheet. However, when the coating density is increased to 300 g / m 2 and 400 g / m 2 Under the circumstances, the high coating density will make the volatilization path of the solvent more complex, the difficulty of solvent migration will increase, and there will be obvious differences in the drying rates on the surface and inside of the electrode sheet, resulting in cracking of the negative electrode sheet of the battery.
[0192] For 1,3-butanediol, it belongs to a kind of small molecule plasticizer, which can dissolve in the solvent and play a lubricating role between molecules, making the film formed by the negative electrode slurry of the battery on the substrate surface have better flexibility, thereby inhibiting the cracking of the electrode sheet to a certain extent. However, if 1,3-butanediol is to improve the flexibility of the film on the substrate surface, it needs to be added in large amounts in the negative electrode slurry of the battery, resulting in that after the baking of the negative electrode sheet of the battery is completed, it may contain more non-battery active materials, which will affect the battery kinetic performance. And when its addition amount is the same as that of the additive in Example 1 of the present invention, both being 0.1%, when the coating density is increased to 300 g / m 2 and 400 g / m 2 Under the circumstances, it cannot resist the influence of the drying rate difference on the surface and inside of the electrode sheet during the solvent volatilization process, resulting in cracking of the negative electrode sheet of the battery.
[0193] However, the additive provided in the embodiment of the present invention cannot be dissolved in the solvent when compared with N-methylpyrrolidone added in Comparative Example 2 and 1,3-butanediol added in Comparative Example 3. It mainly generates a capillary suspension effect in the solvent, enabling the additive to be uniformly dispersed in the solvent. By jointly wetting the negative active material particles with the additive and the solvent, the negative active material particles tend to be dispersed at the two-phase interface between the additive and the solvent. At the same time, the additive can fill the voids between the negative active material particles to form a liquid bridge. Through the action of the liquid bridge, the negative active material particles can be interconnected to form a chain-like network, further enhancing the interaction force between the negative active material particles. The interaction force between the negative active material particles can effectively resist the influence of the drying rate difference on the surface and inside of the electrode sheet during the solvent volatilization process. When the coating density is increased to 300 g / m 2 and 400 g / m 2 , only a small amount of addition is required to effectively avoid cracking on the surface of the negative electrode sheet of the battery. The effect is significantly better than that of Comparative Example 2 and Comparative Example 3.
[0194] It can be seen that in the embodiment of the present invention, by dispersing an additive incompatible with the solvent in the solvent and jointly wetting the negative active material particles with the additive and the solvent, the cracking of the electrode sheet is effectively improved, and ultra-high areal density coating of the negative electrode slurry of the battery can be achieved.
[0195] Porosity test
[0196] For the negative electrode sheets of the batteries prepared in Example 1 and Comparative Example 1, the porosity was measured using an automatic mercury intrusion porosimeter (MIP). The results are shown in Table 2.
[0197] Table 2 Porosity test results
[0198] Example 1 Comparative Example 1 Porosity (%) 57.90% 52.40%
[0199] It can be seen that the porosity of the negative electrode sheet of the battery prepared in Example 1 of the present invention can be higher than that of Comparative Example 1. This is because a chain-like network is formed by the interconnection of the negative active material particles in the embodiment of the present invention. And during the evaporation process of fabricating the negative electrode sheet of the battery using the thick coating process subsequently, the chain-like network can play a supporting role during the drying process of the negative electrode sheet of the battery, enabling the overall negative electrode sheet of the battery to maintain a good pore structure, thereby increasing the porosity of the finally fabricated negative electrode sheet of the battery.
[0200] The above has introduced in detail the battery negative electrode paste provided by the present invention, its preparation method, the negative electrode sheet, the battery and the electrical equipment. Specific examples are used in this article to elaborate on the principle and implementation manner of the present invention. The description of the above embodiments is only used to help understand the method and its core idea of the present invention; at the same time, for those of ordinary skill in the art, according to the idea of the present invention, there will be changes in the specific implementation manner and application scope. In summary, the content of this specification should not be construed as a limitation to the present invention.
Claims
1. A battery negative electrode paste, characterized in that, The negative electrode paste of the battery includes a paste core component and a solvent, and the paste core component includes negative electrode active material particles and an additive; Wherein, the additive is dispersed in the solvent and is incompatible with the solvent; the additive and the solvent jointly wet the negative electrode active material particles, so that the negative electrode active material particles are dispersed at the two-phase interface of the additive and the solvent.
2. The negative electrode paste for a battery according to claim 1, characterized in that The ratio between the contact angle of the additive on the negative electrode active material particles and the contact angle of the solvent on the negative electrode active material particles is 1 / 4 - 1.
3. The battery negative electrode paste according to claim 1 or 2, characterized in that The contact angle of the additive on the negative electrode active material particles is 30° - 75°.
4. The battery negative electrode paste according to claim 1, characterized in that, The additive includes a polyether compound and / or a long-chain oligo-hydroxy alcohol compound.
5. The battery negative electrode paste according to claim 4, characterized in that, The polyether compound includes at least one of polyether, polyethylene oxide, and polyether modified product, and / or the long-chain oligo-hydroxy alcohol compound includes polymer oligol; wherein, the polyether modified product includes at least one of polyether modified silicone oil, polyether modified fluorosilicone oil, and fluorine modified polyether.
6. The battery negative electrode paste according to any one of claims 1-5, characterized in that, The weight average molecular weight of the additive is 200 - 4000.
7. The battery negative electrode paste according to any one of claims 1-5, characterized in that, The mass percentage of the additive in the paste core component is 0.05% - 0.5%.
8. The cathode paste for battery according to claim 7, wherein The mass percentage of the additive in the paste core component is 0.08% - 0.2%.
9. The negative electrode paste according to claim 1, wherein The mass ratio between the paste core component and the solvent is 4:6 to 6:
4.
10. The negative electrode paste for an electrode according to claim 1, characterized in that, The negative electrode active material particles include one or a combination of natural graphite, artificial graphite, soft carbon, and hard carbon, wherein the artificial graphite includes at least one of petroleum coke graphite, needle coke graphite, coated graphite, and mesophase carbon microspheres.
11. The negative electrode paste according to claim 1, wherein, The paste core component further includes one or a combination of a dispersant, a conductive agent, and a binder.
12. A method for preparing the battery negative electrode paste according to any one of claims 1 to 11, characterized in that, The method includes: Mixing the negative electrode active material particles and the solvent to obtain a mixture; Adding an additive to the mixture to obtain the negative electrode paste of the battery.
13. A method for preparing a negative electrode sheet of a battery, characterized in that, The method includes: Coating the negative electrode paste of the battery on a preset negative electrode current collector; wherein, the negative electrode paste of the battery is the negative electrode paste of any one of claims 1 to 11, or the negative electrode paste of the battery is prepared by the preparation method of the negative electrode paste as claimed in claim 12; Drying the negative electrode substrate coated with the negative electrode paste of the battery to obtain a negative electrode sheet of the battery.
14. A battery, characterized in that, The battery includes the negative electrode sheet of the battery as claimed in claim 13.
15. A battery assembly, characterized in that, The battery assembly includes the battery as claimed in claim 14.
16. An electrical device, characterized in that, The electrical equipment includes the battery as claimed in claim 14.